The CD1 family: serving lipid antigens to T cells since the Mesozoic era - Zajonc, Dirk M. (Immunogenetics, 2016)
Class I-like CD1 molecules are in a family of antigen-presenting molecules that bind lipids and lipopeptides, rather than peptides for immune surveillance by T cells. Since CD1 lacks the high degree of polymorphism found in their major histocompatibility complex (MHC) class I molecules, different species express different numbers of CD1 isotypes, likely to be able to present structurally diverse classes of lipid antigens. In this review, we will present a historical overview of the structures of the different human CD1 isotypes and also discuss species-specific adaptations of the lipid-binding groove. We will discuss how single amino acid changes alter the shape and volume of the CD1 binding groove, how these minor changes can give rise to different numbers of binding pockets, and how these pockets affect the lipid repertoire that can be presented by any given CD1 protein. We will compare the structures of various lipid antigens and finally, we will discuss recognition of CD1-presented lipid antigens by antigen receptors on T cells (TCRs).